Escherichia coli mutants with altered ribosomal ribonucleic acid metabolism. - Jackson, J M (1976)
This paper reports the partial characterization of two temperature-sensitive mutants of Escherichia coli with alterations in ribosomal ribonucleic acid (rRNA) metabolism at the restrictive temperature. Both mutants continue to synthesize deoxyribonucleic acid and protein at 42 C but showed little or no accumulation of RNA. Both strains are inducible for beta-galactosidase at the restrictive temperature, showing that messenger RNA synthesis continues and that the messenger RNA is translated into functional protein. One of the strains, 2S474, shows a rather severe depression (sevenfold) in the synthesis of all classes of RNA at 42 C. In addition, the synthesis of rRNA is selectively depressed, with the percentage of rRNA synthesis. However, there appears to be a selective depression in the rate of rRNA synthesis and, possibly, in the conversion of p16S rRNA to m16S rRNA.